2023
DOI: 10.1002/cbdv.202200210
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally‐Friendly Pesticidal Activities ofCallicarpaandKaromiaEssential Oils from Vietnam and Their Microemulsions

Abstract: There is an ongoing interest to identify alternative pesticidal agents to avoid the chronic problems associated with synthetic pesticides. Essential oils have shown promise as botanical pest control agents. In the present study, the essential oils of four members of the Lamiaceae (Callicarpa candicans, C. erioclona, C. macrophylla, and Karomia fragrans; Vietnamese names: Nàng nàng, Tu châu lông mem, Tu châu lá to and Cà diện, respectively), obtained from wild populations in Vietnam, have been obtained by hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…23 According to the criteria of AutoDock4, lower binding free energy values indicate higher stability for the complex and favoring interaction of ligand within the binding site when it predicts the docking pose. 24,25 Table 5 presents the docking results of studied compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 According to the criteria of AutoDock4, lower binding free energy values indicate higher stability for the complex and favoring interaction of ligand within the binding site when it predicts the docking pose. 24,25 Table 5 presents the docking results of studied compounds.…”
Section: Resultsmentioning
confidence: 99%
“…23 According to the criteria of AutoDock4, lower binding free energy values indicate higher stability for the complex and favoring interaction of ligand within the binding site when it predicts the docking pose. 24,25 As previous studies have reported, the active site of SARS-CoV-2 M pro is constituted by key residues as follows: His41, Met49, Asn142, Gly143, Cys145, His164, Met165, Glu166, Lru167, Pro168, His172, Gln189, Thr190, and Ala191. 26 Binding conformation analysis of PF-07321332 indicate that five H-bonding were created by this compound with Cys145, Glu166, Arg188, Gln189, and Thr190, four among them are essential residues in the active binding region of SARS-CoV-2 M pro .…”
Section: Docking Using Autodockmentioning
confidence: 97%
“…Antennae of dsNlugOBP-injected BPHs completely lost the ability to sense caryophyllene oxide [55,56]. Nguyen et al reported that caryophyllene oxide was ranked highly as a mosquito odorant-binding protein inhibitor (with larvicidal activity) based on its docking scores, and likely docks similar to permethrin [57]. Thus, we hypothesized that caryophyllene oxide has repellent activity against P. xylostella and may affect the odorant-binding protein of P. xylostella.…”
Section: Discussionmentioning
confidence: 96%
“…(E)-Nerolidol did not exhibit toxicity against Biomphalaria glabrata at a concentration of 100 µg/mL [35]. Essential oils containing (E)-β-caryophyllene as the main constituent exhibited potent molluscicidal activities against Gyraulus convexiusculus and Pomacea canaliculata [42,43,114].…”
Section: Molluscicidal Activitiesmentioning
confidence: 97%
“…Protocol 1: Tests for larvicidal activity were performed according to WHO guidelines [129] with modifications according to previous publications [42,43,83,114]. Twentyfive larvae were transferred into 250 mL beakers containing 150 mL of essential oil solutions at concentrations of 100, 50, 25, 12.5, 6.25, 3.125, 1.5, 0.75, 0.375, 0.2, and 0.1 µg/mL; each concentration was repeated four times.…”
Section: Larvicidal Biassaysmentioning
confidence: 99%